Efficient Synthesis of 2-Substituted 4H-3,1-Benzoxazin-4-ones under Microwave Irradiation - RAD-MOGHADAM, KUROSH; MONTAZERI, NASSER (Asian Journal of Chemistry, 2010)
A fast synthesis of 2-substituted 4H-3,1-Benzoxazin-4-ones is achieved from reaction of acetic anhydride with 2-acylaminobenzoic acid under microwave and solvent-free conditions.